The Center for Research Data and Digital Scholarship at the University of Colorado‐Boulder. (21st December 2016) - Knuth, Shelley L.; Johnson, Andrew; Lindquist, Thea; Weiss, Debra; Hamrick, Deborah; Hauser, Thomas; Reynolds, Leslie
Abstract : EDITOR'S SUMMARY The University of Colorado‐Boulder expanded its digital services through the 2016 opening of its Center for Research Data and Digital Scholarship (CRDDS), a collaboration between the libraries and research computing. The aim is to provide a full range of data services, from analytics and visualization through curation, storage and preservation, in addition to education and consultation for both university and community members. Increased data discovery, reuse, access and publication are expected to be among the several advantages to this collaborative effort. The CRDDS will focus on promoting research data management mandated by federal funding agencies and journal publishers, cyberinfrastructure to gain full benefit from big data, education and training through courses and online modules, and digital scholarship to explore tools and methods used throughout the life cycle of a digital project. CRDDS plans to create a seminar and consulting space within the library in addition to digital outreach.